The Effects of Ellagic Acid on Some Biochemical Parameters in the Liver of Rats Against Oxidative Stress Induced by Aluminum - Ozkaya, Ahmet; Celik, Sait; Yuce, Abdurrauf; Sahin, Zafer; Yilmaz, Okkes (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
Antioxidant, anti-inflammatory and anti-carcinogenic effects having Ellagic acid ( 2,3,7,8-tetrahidroksil [1] benzapiranol [5,4,3-CDE] [1] benzopiran-5, 10-dione) pomegranate, raspberry, strawberry, many fruits such as grapes and walnuts grained derivative is a substance found in vegetable polyphenols. Aluminum is known to cause toxic effects on variety organ systems. In this study, the effect of ellagic acid on the liver of rats against oxidative stress induced by aluminum chloride (AlCl3) was investigated. Adult male Sprague-dawley rats were randomly divided in four groups. Control the first group, the second group Ellagic acid group, the third group AlCl3 group, the fourth group was used as AlCl3 + Ellagic acid. Ellagic acid 12 mg/kg dose with the orogastric probe and AlCl3 8.3 mg/kg intraperitoneal was administered as a 55 days every other day. Glutathione (GSH) in the liver, malondialdehyde (MDA), vitamin E levels and glutathione peroxidase (GSH-Px) and catalase ( CAT) activities were determined. While administration of AlCl3 increased the MDA level and CAT activity, it decreased the GSH-Px activity in liver compared those of the control group. The effect of ellagic acid to AlCl3-treated rats decreased the MDA levels and increased GSH, GSH-Px and CAT activities in these samples. According to the data we obtained, a result AlCl3 application against oxidative damage in the liver, which has the potential protective effect of ellagic acid, can be said.
Keywords: Ellagic acid; Antioxidant; Aluminum; Oxidative stress; Vitamin E; Rat